Teenage Conduct Problems: A Lifetime of Disadvantage in the Labour Market? - Sam Parsons; Alex Bryson; Alice Sullivan (Institute of Labor Economics (IZA), 2021)
Using data from two British birth cohorts born in 1958 and 1970 we investigate the impact of teenage conduct problems on subsequent employment prospects through to age 42. We find teenagers with conduct problems went on to spend fewer months both in paid employment, and in employment, education and training (EET) between age 17 and 42 than comparable teenagers who did not experience conduct problems. Employment and EET disadvantages were greatest among those with severe behavioural problems. The 'gap' in time spent in employment or EET by conduct problem status was similar for men and women across cohorts, with only a small part of the gap being attenuated by differences in social background, individual characteristics and educational attainment in public examination at age 16. We discuss the implications of our findings.
Keywords: I12; J20; J64; 330; education; training; disadvantage; educational attainment; labour market; employment; behavioural problems; Rutter